Monkeypox infection and pregnancy in lower and middle-income countries: Precautions & recommendations - Omar Abu-Azzam; Mohammad Abu-Jeyyab; Mohammad Daradkeh; Sadeen Zein Eldeen; Saja Zuaiter; Mohammad Al-Mseadeen; Amer Sindiani; Eman Alshdaifat (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Monkeypox (MPX), an orthopoxviral disease endemic in Africa, is now a public health emergency of international concern (PHEIC) as declared by the World Health Organization in July 2023. Although it is generally mild, the overall case fatality rate was reported to be 3%, and the basic reproduction number (R0) is > 1 in men who have sex with men (MSM, i.e., Portugal (1.4), the United Kingdom (1.6), and Spain (1.8)). However, R0 is < 1 in other settings. In concordance with the smallpox virus, it is also expected to increase the risk of adverse outcomes for both the mother and the fetus. The outcomes of the disease in an immunocompromised state of pregnancy are scary, showing high mortality and morbidity of both mother and fetus, with up to a 75% risk of fetal side effects and a 25% risk of severe maternal diseases. Therefore, it warrants timely diagnosis and intervention. The reverse transcription polymerase chain reaction (RT PCR) test is the standard approach to diagnosis. We summarized the recent findings of MPX on pregnancy, and the associated risk factors. We also give recommendations for active fetal surveillance, perinatal care, and good reporting to improve outcomes. The available vaccines have shown promise for primary disease prevention.